2011
DOI: 10.1177/1363460711399038
|View full text |Cite
|
Sign up to set email alerts
|

BDSM as therapy?

Abstract: While I was conducting field research on professional dominatrices ('pro-dommes'), an unexpected discourse emerged: respondents repeatedly characterized themselves as 'therapists', speaking about their work as a form of psychological treatment for their clients. This article examines the way they speak about BDSM (Bondage, Discipline, Sadism, Masochism) as therapeutic. Data are derived from in-depth, semi-structured interviews with 66 female pro-dommes. The rhetoric used by participants in this form of commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…I just play out of a place of love. (Mistress Natasha) Our findings are consistent with Lindemann's (2011a) in that many pro-dommes in our sample see themselves as providing a therapeutic service. They assert acceptance of 'deviant' sexuality as a central motivation for their work.…”
Section: Empathy Nurturance and Interpersonal Connectionssupporting
confidence: 94%
“…I just play out of a place of love. (Mistress Natasha) Our findings are consistent with Lindemann's (2011a) in that many pro-dommes in our sample see themselves as providing a therapeutic service. They assert acceptance of 'deviant' sexuality as a central motivation for their work.…”
Section: Empathy Nurturance and Interpersonal Connectionssupporting
confidence: 94%
“…Participants in the current study also commonly reported that great sex was a benefit (subsumed under pleasure and arousal), which is congruent with Kleinplatz et al's (2009) finding that sadomasochism practitioners report that they are in a particularly good position to experience optimal sex due to skills learned from BDSM play. The benefit of psychological release was also found by Lindemann (2011) in her study of professional dominatrices and Moser and Levitt's (1987) finding that a majority of BDSM practitioners enjoy BDSM as much as or more than vanilla sexual activity was supported. What Nichols (2006) called exploration and excitement roughly map onto the benefit of fun, variety, and going beyond vanilla, as well as pleasure and arousal.…”
Section: Discussionmentioning
confidence: 65%
“…Nichols (2006), based on her extensive background of more than 20 years providing therapy for kinky clients, proposed numerous advantages of BDSM, such as personal empowerment, improved communication between partners, excitement because of the diversity and taboo nature, and spiritual benefits. It has also been argued to be cathartic, allowing for both physical and mental release; indeed, some professional dominatrices consider their role to be similar to that of a therapist (Lindemann, 2011). Moreover, Kleinplatz (2006) and colleagues (2009) suggests that 'vanilla' couples can learn a great deal from BDSM practitioners, from the importance of communication to the potential for optimal sexual experiences.…”
Section: Introductionmentioning
confidence: 96%
“…Recent criminological, ethnographic and anthropological work on sadomasochistic communities provides a basis for a closer and more grounded analysis of how sadomasochistic activities actually function within subcultural spaces (Beckmann, 2009;Lindemann, 2011Lindemann, , 2012Newmahr, 2008Newmahr, , 2010Newmahr, , 2011Weiss, 2006bWeiss, , 2011. There is a tendency within this body of work to eschew broad generalizing claims about the meaning of sadomasochistic activities tout court and to be more responsive to the specifics of context.…”
Section: Sadomasochism As Context Dependentmentioning
confidence: 99%